Penanggulangan Penanggulangan Kejahatan Keuangan Di Indonesia Melalui Strategi Yang Komperhensif: Penanggulangan Kejahatan Keuangan Di Indonesia Melalui Strategi Yang Komperhensif. - Dewi Asri Puannandini, Dewi Asri Puannandini; Rahma Turisina WD; Alviyanti Azzahra, Alviyanti Azzahra; Fikhri Farhan Mubarok, Fikhri Farhan Mubarok; Renzi Rizky Satria, Renzi Rizky Satria (Jurnal Media Justitia Nusantara, 2025)
Financial crime poses a serious threat to the economic stability and integrity of the financial system in Indonesia, negatively impacting public trust and financial institutions. Addressing this issue requires a comprehensive approach that involves various legal, policy, and inter-agency collaboration aspects. This article discusses the strategic steps that need to be taken, including strengthening the existing legal framework, enhancing human resource capacity, and fostering collaboration among law enforcement agencies such as the Police, Prosecutor's Office, and the Financial Transaction Reports and Analysis Center (PPATK). Additionally, emphasizing public education about financial crimes and the implementation of modern technologies such as big data and artificial intelligence is crucial for detecting and preventing these criminal activities. By identifying existing barriers, such as a lack of understanding, coordination issues, and budget constraints, this article offers recommendations to improve the effectiveness of financial crime prevention efforts. With an integrated and sustainable strategy, it is hoped that Indonesia can create a safer environment for financial management and enhance economic stability. Keywords: Combating Crime, Financial Crime, Comprehensive Strategy.